Die aktuelle Diagnostik der beatmungsassoziierten Pneumonie: Eine Übersicht der Möglichkeiten = Modern-day diagnostics of ventilator-associated pneumonia : an overview of options - Bexten, Tobias; Haarmeyer, G.-S.; Unglaube, M.; Beck, Grietje; Mohr, David (Anästhesiologie & Intensivmedizin, 2025)
Ventilator-associated pneumonia (VAP) is a serious complication in patients who have been ventilated for at least 48 hours. It has an incidence of up to 67 %, making it one of the most common complications in intensive care units. It is associated with increased mortality, prolonged ventilation and very high treatment costs.